(untitled) (RT. A Journal on Research Policy and Evaluation, 2013)
Writing for peer-reviewed research journals is difficult and requires specialized skills and knowledge—in language, logical argumentation, data presentation, publication ethics and more. The task is especially challenging for researchers who use English as an additional language. In this discussion paper, I illustrate how research writing in non-anglophone settings can usefully be supported by three types of language professional: teachers of academic writing, authors’ editors, and academic translators. Reviewing the situation in Italy, I observe that Italian researchers have limited access to the best forms of writing support, in part due to misconceptions and complex hiring rules. Finally, and based on the higher educational trends in northern Europe, I envisage a future scenario for Italy where university-wide academic writing centers will be established, language professionals with disciplinary knowledge will become part of research institutes’ staff, and researchers will have facilitated access to the services of authors’ editors and academic translators on a per-manuscript basis. As research writing support becomes integrated into the university setting, Italian researchers’ productivity will increase and the profile of Italian reporting in the international literature will be raised.